2013
DOI: 10.1007/s10493-013-9711-9
|View full text |Cite
|
Sign up to set email alerts
|

Potential of the predatory mite Phytoseius finitimus (Acari: Phytoseiidae) to feed and reproduce on greenhouse pests

Abstract: Phytoseiid mites of the genus Phytoseius are natural enemies of tetranychid and eriophyid herbivorous mites mostly found on hairy plants where they feed on prey, as well as on pollen. Nevertheless, the nutritional ecology and the role of these predators in biological pest control are only rarely addressed. In the present study, we evaluated the potential of Phytoseius finitimus to feed and reproduce on three major greenhouse pests, the two-spotted spider mite, the greenhouse whitefly and the western flower thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 46 publications
2
17
0
4
Order By: Relevance
“…Mixed diets consisting of two or more prey species or a mixture of pollen with prey have been shown to increase the numerical response of phytoseiid predators on prey of both high- (Nomikou et al, 2002(Nomikou et al, , 2010van Rijn et al, 2002) and low-quality (Messelink et al, 2010). Therefore, in theory, high quality pollen combined with low quality prey would positively affect biological control even in the event of decreased prey consumption per capita on the unsuitable prey (Pappas et al, 2013). On the other hand, variations in the quality of plant food (pollen) may differentially affect the numerical response of the predator on a specific prey (Samaras, 2018) and the same holds for the quality of prey.…”
Section: Introductionmentioning
confidence: 99%
“…Mixed diets consisting of two or more prey species or a mixture of pollen with prey have been shown to increase the numerical response of phytoseiid predators on prey of both high- (Nomikou et al, 2002(Nomikou et al, , 2010van Rijn et al, 2002) and low-quality (Messelink et al, 2010). Therefore, in theory, high quality pollen combined with low quality prey would positively affect biological control even in the event of decreased prey consumption per capita on the unsuitable prey (Pappas et al, 2013). On the other hand, variations in the quality of plant food (pollen) may differentially affect the numerical response of the predator on a specific prey (Samaras, 2018) and the same holds for the quality of prey.…”
Section: Introductionmentioning
confidence: 99%
“…They can exploit food sources such as honeydew, plant-based substances and fungi (e.g., Gnanvossoua et al 2005;Nomikou et al 2003;van Rijn and Tanigoshi 1999;Pozzebon and Duso 2008;Pozzebon et al 2009;Pappas et al 2013). The importance of pollen as an alternative food has been extensively proved (e.g., Overmeer 1985;McMurtry and Rodriguez 1987;McMurtry et al 1991;.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the western flower thrips Frankliniella occidentalis (Pergande) (Thysanoptera: Thripidae) feeds on plant material and arthropod prey, leading to its role as both a serious pest (Grazia-Tommasini, 1995; Kirk and Terry, 2003) and a biological control agent (Trichilo and Leigh, 1986; Wilson et al, 1996; Agrawal and Karban, 1997; Milne and Walter, 1997). Furthermore, Agrawal et al (1999) revealed that the presence of prey [eggs of the Pacific spider mite Tetranychus pacificus McGregor (Thysanoptera: Tetranychidae)] reduced feeding by F. occidentalis on cotton by nearly 50%.…”
Section: Impact Of Plant Traits On Biological Controlmentioning
confidence: 99%